Fuzzy-neuro system for decision-making in management - Setlak, G. (Системні дослідження та інформаційні технології, 2003)
This paper introduces a systematic approach for intelligent decision support system design based on a class of neural fuzzy networks built upon a general neuron model. The neural fuzzy networks can formally represent and process both the qualitative (linguistic) and quantitative information, which usually describe a complex, multidimensional systems or decision making processes. Presented the results of tests and a practical implementation of applications of fuzzy-neuro system for decision-making in strategic management and determination of product development strategy.